PSYCHOLOGICAL INTERPRETATION OF THE PHENOMENON OF HAPPINESS IN THE PROCESS OF PERSONAL SELF-REALIZATION (World Bulletin of Social Sciences, 2023)
In the article, the behavior of a person in the process of selfrealization in order to live his life meaningfully and happily, philosophical approaches to the problem of happiness, the high value of life, the triggers of relaxation, feeling the pleasure of the body, the attributes of happiness: a spacious house, abundance of clothes, the meaning of things and beautiful things as a psychological reality. it is about the fact that it is made up of processes that require each other.